1994
DOI: 10.1002/jsfa.2740650314
|View full text |Cite
|
Sign up to set email alerts
|

Cassava retting: Optimisation of a traditional fermentation by an experimental research methodology

Abstract: Retting, a spontaneous and traditional fermentation of cassava roots in Central Africa, was optimised in terms of time and the quality of the endproduct. Optimal conditions were achieved by using an experimental research methodology. Temperature is the most influential factor, with an optimum of 34°C for quicker retting. The roots should be peeled and soaked in water immediately after harvesting to increase the quality of cassava foods. Inoculation of water with juice from a prior retting helps in cassava deto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
3

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
0
14
0
3
Order By: Relevance
“…o15 mm) during the first 48 h of fermentation for the production of Nigerian fufu, which also affected product organoleptic qualities (Oyewole, 1994). The reduction in cyanogen levels has been found to be strongly correlated to the degree of root size reduction, which is also directly related to the rate of softening and acidification (O'Brien et al, 1992;Ampe et al, 1994;Westby and Choo, 1994).…”
Section: Effects Of Root Size Reduction and Soakingmentioning
confidence: 99%
See 1 more Smart Citation
“…o15 mm) during the first 48 h of fermentation for the production of Nigerian fufu, which also affected product organoleptic qualities (Oyewole, 1994). The reduction in cyanogen levels has been found to be strongly correlated to the degree of root size reduction, which is also directly related to the rate of softening and acidification (O'Brien et al, 1992;Ampe et al, 1994;Westby and Choo, 1994).…”
Section: Effects Of Root Size Reduction and Soakingmentioning
confidence: 99%
“…Cooke (1979) reported that the optimum pH and temperature of linamarase activity are 5.5-6.5 and 30 1C, respectively. It has been observed that soak-water temperatures of 30-37 1C caused high rates of acidification, shorter periods of soaking (at least 60 h), high cyanogen reduction levels and acceptable product organoleptic qualities (Oyewole and Odunfa, 1992;Ampe et al, 1994). Studies on Nigerian lafun and fufu production have shown that a soaking period of about 40-60 h and temperature range of 30-35 1C were best conditions for submerged fermentation products, while other variables such as root size, age of the roots, and changing of the soak waters have effects on product quality (Oyewole, 1994).…”
Section: Role Of Soak-water Conditionsmentioning
confidence: 99%
“…Retting of cassava entails steeping roots in water for 3 to 4 days. During the consequent fermentation, roots are softened (34), the endogenous cyanogenic glycosides (linamarin and lotaustralin) are degraded (3), and characteristic flavors develop (1,36). In the West and in Asia, retting is used for the treatment of certain Malvaceae, such as linen flax (7), and other plants, such as cucumber (39).…”
mentioning
confidence: 99%
“…These products provide almost 50% of the caloric intake of the population (47). Despite the economic importance of these processed products, most of the published work on cassava retting has focused on the detoxification of the cyanogenic glycosides during fermentation (2,3,14,27) or the influence of bacterial inoculation on foo-foo flavor and root softening (1,34,36). In previous studies on the microbiological aspects of this fermentation for production of foo-foo (34) or related products (9,37), aerobic or air-tolerant microorganisms were counted or isolated but strict anaerobes were not considered.…”
mentioning
confidence: 99%
“…Durante a fermentação da puba, Almeida et al (1987), verificaram que o processo fermentativo pode ser acelerado empregando-se em vez das raízes inteiras, pequenos fragmentos colocados em água a temperaturas próximas a 30ºC. Trabalhos realizados para obtenção de fufu por Okafor et al (1984) sugerem que o tamanho da raiz afeta a velocidade de maceração, porém Ampe et al (1994), trabalhando com raízes inteiras concluíram em seus experimentos que esse fator não tem efeito significativo na velocidade deste processo. Assim como outras variáveis como o tempo de estocagem, a retirada da película externa e a variedade da mandioca parecem ter pouca ou nenhuma influência na velocidade de maceração para produção de fufu.…”
Section: Aspectos Físico-químicos Da Fermentaçãounclassified